THE INFLUENCE OF ETHICAL LEADERSHIP ON COMPANY PERFORMANCE (CASE STUDY: AT PTPN I BEFORE MERGER REGIONAL 1 SUPPORT INC ) - Pratiwi, Henny; Sugianto, Sugianto (PT. Jurnal Center Indonesia Publisher, 2025)
Based on the research results, the research results show that ethical leadership supports the adoption of positive behavior by employees and overall improves organizational performance. This approach emphasizes the ethical dimension of leadership in the context of management, with a focus on improving leader values, ethical traits and ethical behavior within the organization. Aspects such as Telling, Selling, Participating & Delegating are considered key elements in ethical leadership . The method used is multiple regression analysis, an analysis method used to evaluate the relationship between one dependent variable (bound) with one or more independent variables (free/explanatory). This analysis aims to predict the value of the dependent variable by considering changes in the value of the independent variable. In addition, multiple regression analysis helps in determining the direction of the relationship between the dependent variable and the independent variable, whether the correlation is positive or negative. The regression equation formula for two dependent and independent variables . The tests used are classical assumption tests, hypothesis tests and data quality tests. The sample is determined by taking a representation of the population that is predicted to represent the entire population. The sample in this study were employees at the PT. Perkebunan Nusantara (Persero) I Office Regional I . Determination of samples for employees of PT. Perkebunan Nusantara I (Persero) Regional I was carried out using the Saturated Sampling method . The results of the study showed that X1 telling t count -1.113 < t table 5.409 and significance 0.316 > 0.05 (no effect). X2 selling t count -0.365 < t table 5.409 and significance 0.730 > 0.05 (no effect). X3 participation t count 8.090 > t table 5.409 and significance 0.010 < 0.05 (influential). X4 delegation t count 9.320 > t table 5.409 and significance 0.000 < 0.05 (influential). The results of the simultaneous significance test of the F test are f count 6.076 > f table 5.409 and the prob (F-statistic) is 0.0000 < 0.05. H0 : β1 = β2 = • • • = βk = 0 This means that the independent variable has an overall influence/relationship on the dependent variable